The role of diet and housing-temperature in the production of genetically modified mouse embryos and their developmental capacity after cryopreservation - Ramin, Michael Tobias André; Denk, Nora; Schenkel, Johannes (Theriogenology, 2015)
Mutant mouse lines are unique models with an enormous scientific potential. Cryopreservation of preimplantation embryos or of spermatozoa is a common approach to save those lines. The breeding of a line can be discontinued if sufficient specimens have been cryopreserved. Prerequisites to economically cryopreserve embryos are high yields of embryos prepared from donors and a high recovery rate after revitalization. Diets for laboratory animals are often produced from phytoestrogen-containing soy; the present study shows that feeding the donor animals with a phytoestrogen-poor diet is more efficient compared to a phytoestrogen-containing, soy-based diet. Additionally, a uterotrophic bioassay indicating the estrogenic role of compounds showed a significant increase of the relative uterus size of females fed with a phytoestrogen-rich diet. The role of the housing-temperature was investigated, too, showing that a housing-temperature of 24 °C results in the best embryo yields. The production of two-cell embryos is more economic than the production of eight-cell embryos. Investigating the recovery rate of frozen/thawed embryos, a very high recovery rate was determined when both, two- and eight-cell embryos were thawed. However, the capacity to develop to the next embryonic stage in vitro was dramatically reduced when two-cell embryos were compared to eight-cell embryos. After embryo transfer, the sex ratio became uneven and more males were delivered. This effect might be due to the procedures to which animals and embryos were subjected. These data show that many parameters can influence the production of animals when using (frozen/thawed) embryos. These parameters need continuous surveillance.